Traduire le "spoken word" : deux poèmes de Jacob Sam-La Rose et leur traduction française - Bastien Goursaud; Jacob Sam-La Rose (Sillages Critiques)
On 5 October 2018, Jacob Sam-La Rose was invited by VALE, POEM (Sorbonne Nouvelle) and Sorbonne Université to perform his poems at the Institut du Monde Anglophone in Paris.The performance was held in the main lecture hall of the Institut du Monde Anglophone, in Paris, an unlikely venue for a spoken word event. Yet Sam-La Rose’s wit and his enthusiastic use of the hall’s acoustics made for a memorable performance, one that certainly made the poems “take place.” In order to record something of that special part of the conference, Jacob Sam-La Rose has agreed to let me translate two of the poems he performed.